Analysis Performance of Income and Expenditure of Social Health Insurance in Indonesia: Legal Description and Data Frame For Indonesia Finance Health Care Projection - A, Firmansyah Y (Jurnal Manajemen dan Keuangan, 2004)
The objective of this research was to analyze the performance of Social Health Insurance in Indonesia that applied to the efficiency and sustainability of the schema. Whereas, it covered the compulsory and voluntary members from the public employee and all Indonesian people, therefore the program should be matched to the covered people as a beneficiary and cost of program on the one side to the income from the contribution on the other side. Documentation, literatures, interview, and manual books are used on this research. Beside that some international standars such as Social National Account 1993 (SNA 1993), and Population Model by UN and ILO are also referred, when the projection were done. The results showed that the projection methods, which used 50 years projection, indicated an increasing of employed people followed by the covered people and demand for health services continues rise. However, Since economic crisis in 1997, evidenced in dramatic reductions Â in GDP growth rates, the emphasis in some countries especially in Indonesia has shifted from expanding services and improving quality to attempting simply to maintain the level of existing services. Thus, the sustainability and cost containment efforts of health systems have become the major challenges, and financing is a critical element in meeting these challenges. The emphasis in health care financing today has shifted to cost containment through efficiency gains in exiting system, while finding effective mechanism for funding the overall system in a long-term, sustainability fashion. Therefore, the scheme and program performance are able to support the government in order to apply a policy.Key Words: Efficiency, sustainability, cost containment, contribution